Checking for understanding : formative assessment techniques for your classroom - Fisher, Douglas, 1965-; Frey, Nancy, 1959- (Alexandria, VA : ASCD, 2007)
Offers advice to teachers on how to use creative formative assessments to determine whether students are understanding lessons they receive in the classroom.
Why check for understanding? -- Using oral language to check for understanding -- Using questions to check for understanding -- Using writing to check for understanding -- Using projects and performances to check for understanding -- Using tests to check for understanding -- Using common assessments and consensus scoring to check for understanding.
Includes bibliographical references (p. 141-149) and index.
Professional
Keywords: Classroom management; Effective teaching; Classroom management; Teaching